Sustainable Consumption and Production Patterns: Policy Design and Evaluation - Hotta, Yasuhiko; Tasaki, Tomohiro; Managi, Shunsuke (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is intended to highlight why SCP policy design and evaluation needs to overcome conventional environmental policy framework. Emerging SCP policy design and evaluation do not involve focusing on individual products or behaviors or improving efficiency in management systems in relation to environmental sustainability; instead, they address more socio-economic systems and target collective efforts for transition. Effort has been made for this book/Special Issue to feature studies contributing to policy design and evaluation in this direction. It contains 11 papers covering challenges and opportunities for SCP policy design, application of foresight to policy design, evaluation of NDC potentials to facilitate sustainable lifestyles, comparative analysis of sustainable development criteria, sustainable lifestyle and education, subjective wellbeing and sustainable consumption, case studies on challenges and opportunities for sustainability transition at the local and community level, and three case studies on how to fill gaps between policy goals and environmental behavior at a city level in China, Vietnam, and Thailand. The papers in this book suggest that SCP policy design and evaluation need to pay more attention to social aspects of sustainability such as social infrastructure and well-being and socio-technical systems to ensure effective and just transition to sustainability.